2023
DOI: 10.3389/fmolb.2023.1254834
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of Alzheimer’s disease-related biomarkers in plasma and neuron-derived extracellular vesicles: a nested case-control study

Apostolos Manolopoulos,
Francheska Delgado-Peraza,
Maja Mustapic
et al.

Abstract: Introduction: Alzheimer’s disease (AD) is currently defined according to biomarkers reflecting the core underlying neuropathological processes: Aβ deposition, Tau, and neurodegeneration (ATN). The soluble phase of plasma and plasma neuron-derived extracellular vesicles (NDEVs) are increasingly being investigated as sources of biomarkers. The aim of this study was to examine the comparative biomarker potential of these two biofluids, as well as the association between respective biomarkers.Methods: We retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…3 A). In a similar study by A. Manolopoulos et al [ 66 ], they studied levels of Aβ42, total Tau, and pro-brain-derived neurotrophic factor (BDNF) in both plasma neuron-derived extracellular vesicles (NDEVs) and plasma. The study reported a lack of correlation between the plasma and NDEVs, substantiating concerns about levels of the Aβ42 and total Tau measured in plasma originating from non-CNS sources.…”
Section: Discussionmentioning
confidence: 99%
“…3 A). In a similar study by A. Manolopoulos et al [ 66 ], they studied levels of Aβ42, total Tau, and pro-brain-derived neurotrophic factor (BDNF) in both plasma neuron-derived extracellular vesicles (NDEVs) and plasma. The study reported a lack of correlation between the plasma and NDEVs, substantiating concerns about levels of the Aβ42 and total Tau measured in plasma originating from non-CNS sources.…”
Section: Discussionmentioning
confidence: 99%
“…We will also investigate correlations between plasma biomarkers, neuroimaging markers and cognitive features. Analytes will be multiplexed using Invitrogen ProcartaPlex assay (Thermo Fisher, USA)[ 40 ] using the Bioplex 200 instrument platform (Bio-rad, California, USA) which employs a bead-based multiplex assay to allow simultaneous detection of multiple analytes within a single sample. It involves coupling capture antibodies of target analytes to fluorescent beads, incubating them with the plasma samples, and then detecting bound proteins using fluorescently labelled detection antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Goetzl et al [ 13 ] and Agliardi et al [ 1 ] found the reduced levels of neuronal proteins with known synaptic functions in plasma neural-derived exosomes (NDEs) of AD patients compared to healthy controls (HC). Lately, Manolopoulos et al identified plasma neuron-derived extracellular vesicles-associated Aß42/40 ratio and proBDNF (with good correlations with MMSE scores) as possible biomarkers for AD diagnosis and monitoring [ 28 ]. Kumar et al found that miRNA of brain cell-derived small extracellular vesicles correlated with the temporal cortical region thickness on magnetic resonance imaging (MRI) and could serve as a novel blood-based molecular biomarker for AD [ 26 ].…”
Section: Introductionmentioning
confidence: 99%